(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2023)
The present work deals with the first artistic works that can be understood as "masking" of bodies or costumes made with electronic or digital technologies. Regarding "wearable technologies", we can understand them as prostheses and extensions not only of our physical capacities (such as glasses or a cane), but also as cognitive ones, the extension of memory and subjectivity as a form of artistic expression. The investigation was based on interviews conducted in 2015 with Luisa Paraguai about her work "Vestis" (2005) and Otávio Donasci about her dynamic mask-costumes "Videocriaturas" (1980). Both works recognize the difficulties and obstacles in relation to technical procedures, as well as an extremely current expression in contemporary debates. Among them, the role of inanimate items (such as electronic and digital technologies) with an important agency role that modulates the relationships between our bodies, society and the environment.